Silvopastoral and peasant management effects on vegetation and soil quality in the arid chaco of central Argentina. (November 2022) - Marquez, Victoria; Carbone, Lucas M.; Chiapero, Ana L.; Ashworth, Lorena; Calviño, Ana A.; Zamudio, Fernando; Aguilar, Ramiro
Abstract: Nowadays the arid Chaco in central Argentina presents gradients of woody vegetation cover with a variety of management regimes with different environmental impacts. Here, we compare the relative effects of the two most widespread management systems in the region: silvopastoral and peasant managements. Soil properties, plant species richness, composition and vegetation structure were used as ecological indicators as they are crucial for long term-sustainability of production systems. Vegetation cover and plant composition responded differently to land management systems. While plant species richness and composition remained similar in both land management types, tree cover showed a strong reduction in silvopastoral systems. We also observed differences in soil properties, with increases in nitrates, sulfates and electrical conductivity in silvopastoral systems as compared to peasant land management. Tree cover reduction and higher soil salinity may impact negatively the productive capacity of soils, which may compromise the delivery of ecosystem services in silvopastoral systems of central Argentina in the long-term. Peasant land use management showed comparable less environmental impact on soils, allowing the preservation of not only provision services but also of regulating and supporting services in these highly vulnerable areas. Highlights: Environmental effects of silvopastoral and peasant systems have never been compared. Plant species composition remained similar between management systems. Tree cover and soil quality decreased in silvopastoral sites while bare soil increased. Increased soil salinity can risk sustainability of silvopastures in arid chaco. Peasant systems had lower impact on these environmental indicators.